1979
DOI: 10.1016/s0022-5347(17)56881-0
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Evaluation of Patients with Calcium Urolithiasis

Abstract: Eighty patients with proved calcium urolithiasis participated in an outpatient study designed to define the most likely metabolic problem related to the cause of the stone disease. Diagnostic categories included absorptive hypercalciuria (33 patients), renal leak hypercalciuria (20 patients), hypomagnesiumuria (27 patients), hyperuricemia and hyperuricuria (16 patients), hyperoxaluria (15 patients), normal stone-former (4 patients), renal tubular acidosis (2 patients) and suspicion of hyperparathyroidism (7 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0
3

Year Published

1982
1982
1998
1998

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 11 publications
1
3
0
3
Order By: Relevance
“…This yields several advantages including more reliable insight in dietary habits of the patients, lower costs, less loss of work and better compliance. This contention is in agreement with other experienced laboratories and centers, which have followed a great number of patients with CaNL [9, 10, 11]. In order to improve the accuracy of metabolic studies some advise making three 24-hour urine collections and blood sampling.…”
Section: Laboratory Investigationssupporting
confidence: 78%
“…This yields several advantages including more reliable insight in dietary habits of the patients, lower costs, less loss of work and better compliance. This contention is in agreement with other experienced laboratories and centers, which have followed a great number of patients with CaNL [9, 10, 11]. In order to improve the accuracy of metabolic studies some advise making three 24-hour urine collections and blood sampling.…”
Section: Laboratory Investigationssupporting
confidence: 78%
“…It is known that recurrences are common in patients who form calcium oxalate (CaOx) stones (Ljunghall, 1977;Johnson eta/., 1979;Sutherland, 1982) and it is accepted that prophylactic measures should be taken to prevent further stone formation or to reduce the recurrence rate (Rose, 1979;Drach et a/., 1979;Peacock and Robertson, 1980;Bach and Vahlensieck, 1980;Blomen and Bijvoet, 1983;Yendt, 1983).…”
mentioning
confidence: 99%
“…Since uri nary Ppi and GAG determinations are not routine for many clinicians [ 13] Various series showed that the average level for cal cium stone patients was above 2 mmol/24 h [3, 7-11], Our average of 1.3 mmol/24 h is markedly lower. On the other hand the incidence of citrate deficiency among stone patients varies between 29.2 and 63% [12,13], The overall incidence of hypocitraturic urolithiasis in our series is 46.56% and represents the highest rate for any etiological factor. It is also important to note that our patients with uric acid, infective stones and hypercalci uria showed an even higher hypocitraturia rate concomittantly.…”
mentioning
confidence: 55%
“…Yet this should be no reason for not determining at least some of them routinely or for preserving the determinations for recurrent stone pa tients as advocated by some authors [17,18]. Reports by Pak et al [ 19] and Drach et al [ 12] underline the impor tance of these measurements in delineating a very high number of patients in whom an augmentation type of prophylaxis is very effective in lowering new stone for mation. Additionally Pak [20] reported that all patients, including first-time stone formers, should undergo diag nostic evaluation because patients with single renal stone occurrence have equally severe biochemical abnormali ties as recurrent patients.…”
mentioning
confidence: 99%